Bifurcation conditions for the solutions of weakly perturbed boundary-value problems for operator equations in Banach spaces - Zhuravlev, V. F. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We obtain bifurcation conditions for the solutions of weakly perturbed boundary-value problems for operator equations inBanach spaces from the point $ε = 0$. A convergent iterative procedure is proposed for the construction of solutions as partsof series in powers of $ε$ with pole at the point $ε = 0$.